Proposição de um método para implantação de um programa de padronização de componentes - Baccin, Bruno Miguel (Universidade do Vale do Rio dos Sinos, 2017)
The intensification of competitiveness in the industrial environment, related to the phenomenon of globalization, directs organizations to continuously seek to optimize their businesses. A market made up of increasingly demanding customers from the point of view of prices, service, quality and technology, coupled with a competition with international companies tends to present difficulties for the competition of Brazilian companies. This economic scenario points to the intensification of competition by increasing the variety of products and reducing the size of manufacturing lots. The theoretical framework seeks to present the main theoretical aspects about the impact that the variety of products has on the productive systems and also the main methodologies and techniques that help in the understanding and standardization of the component portfolio. From this scenario, the present work proposes a general method for the implementation of a standardization program whose objective is to help reduce the variety of components while maintaining the same diversity of products offered to the market. The research method was Design Research and the empirical stage of the work was carried out in a metal-mechanic company located in Farroupilha (RS). The proposed method was based on five sources of information: i) the concepts and techniques existing in the literature; ii) theoretical propositions of the research; iii) empirical knowledge of a group of experts, who evaluated the method before its application; iv) contribution of the professionals of the company and the researcher himself from the application of the method; and v) the evaluation of the method from the application of the same in business environment. At the end of the study, a final method proposal was made available for new applications.
Keywords: Padronização; Redução de variedade; Design research; Standardization; Reduction of variety; Design research; ACCNPQ::Engenharias::Engenharia de Produção